Influence of Respiratory Muscle Training on Patients’ Recovery after Lung Resection - Kendall, Filipa; Silva, Gustavo; Almeida, João; Eusébio, Ermelinda; Pinho, Paulo; Oliveira, Jose; Bastos, Pedro Teixeira (International Journal of Sports Medicine, 2020)
This prospective experimental study aimed to compare effects of 3 different home-based postoperative respiratory muscle training protocols – inspiratory, expiratory and combined, in the patients’ postoperative recovery, regarding safety and respiratory muscle function, pulmonary function, physical fitness, physical activity (PA), dyspnoea and quality of life (QoL). Patients were divided in four groups Usual Care (UCare), inspiratory (IMT), expiratory (EMT) or combined muscle training (CombT) according to group allocation. Significant treatment*time interactions were found for maximal inspiratory pressure (MIP) (p=0.014), sedentary PA (SEDPA) (p=0.003), light PA (LIGPA) (p=0.045) and total PA (p=0.035). Improvements were observed for MIP in CombT (p=0.001), IMT (p=0.001), EMT (p=0.050). SEDPA reduced in EMT (p=0.001) and IMT (p=0.006), while LIGPA increased in both groups (p=0.001), as well as Total PA (p=0.005 and p=0.001, respectively). In UCare, CombT, and EMT, QoL improved only for Usual Activities. In conclusion, the addition of respiratory muscle training to physiotherapy usual care is safe and effective to increase MIP and contribute to improve physical activity. The CombT showed greater improvement on MIP, while IMT compared to EMT, was more effective to improve physical activity.
Keywords: pulmonary surgery; respiratory muscle training; physiotherapy usual care; maximal inspiratory pressure; physical activity; quality of life